Spatiotemporal evolution of runaway electrons from synchrotron images in Alcator C-Mod. (25th October 2018) - Tinguely, R A; Granetz, R S; Hoppe, M; Embréus, O
Abstract: In the Alcator C-Mod tokamak, relativistic runaway electron (RE) generation can occur during the flattop current phase of low density, diverted plasma discharges. Due to the high toroidal magnetic field ( B 0 = 5.4 T), RE synchrotron radiation is measured by a wide-view camera in the visible wavelength range ( λ  ≈ 400–900 nm). In this paper, a statistical analysis of over one thousand camera images is performed to investigate the plasma conditions under which synchrotron emission is observed in C-Mod. In addition, the spatiotemporal evolution of REs during one particular discharge is explored in detail via a thorough analysis of the distortion-corrected synchrotron images. To accurately predict RE energies, the kinetic solver CODE (Landreman et al 2014 Comput. Phys. Commun. 185 847–855) is used to evolve the electron momentum-space distribution at six locations throughout the plasma: the magnetic axis and flux surfaces q  = 1, 4/3, 3/2, 2, and 3. These results, along with the experimentally-measured magnetic topology and camera geometry, are input into the synthetic diagnostic SOFT (Hoppe et al 2018 Nucl. Fusion 58 026032) to simulate synchrotron emission and detection. Interesting spatial structure near the surface q  = 2 is found to coincide with the onset of a locked mode and increased MHD activity. Furthermore, the RE density profile evolution is fit by comparing experimental to synthetic images, providing important insight into RE spatiotemporal dynamics.